PENINGKATAN KOMPETENSI SEBAGAI STRATEGI PASCA PANDEMI COVID 19 (STUDI KASUS PADA HOTEL XYZ DEPARTEMEN FRONT OFFICE) - Kusuma, Muhammad Eko Abrian; Hartanto, Hartanto; Fauzi, Haliza Nur (Universitas Nusantara PGRI Kediri, 2022)
The COVID-19 pandemic has had an impact on the Indonesian economy, including the hotel sector. Hotel XYZ is one of the four-star visitor hotels in Jakarta which has decreased in number, hotel management is making efforts to be able to rise after the Covid 19 pandemic. This study aims to describe increasing competence as a strategy for XYZ hotel after the covid 19 pandemic, especially the front office department. The research method was carried out qualitatively where the data were obtained through observation, structured interviews with key informants from the company, and documentary techniques. The findings of this study are that efforts to increase the competence of front office employees at Hotel XYZ are carried out with a training approach through the On The Job Training & coaching method and the Off The Job Training method through role play and scheduled discussions with topics/materials based on data from the types of customer complaints. After carrying out the training the number of complaints dropped and guests were satisfied with the services provided.